2008
DOI: 10.2753/ijs0020-7659380403
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Family, and Work: The Case of Poland in Cross-National Perspective

Abstract: The situations of men and women in the labor market in particular countries strongly differ from one another. The differences are loosely related to attitudes concerning work, family life, and gender. This article characterizes Polish social politics and society as a mosaic of traditional and nontraditional values, expectations, and behaviors when it comes to family and work. One of the basic questions is whether new lines of conflict and new spheres of understanding are emerging between women and men as they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 3 publications
0
13
0
1
Order By: Relevance
“…In the case of gender egalitarianism, Poland ranks 42nd of 149 countries in the world in the Global Gender Gap Report (World Economic Forum 2018), and this position is stable since 2006 (44th of 115 countries). Some researchers pointed out that although values and attitudes toward family and work are still changing after the political transformation in Poland, gender roles seem to still be strongly aligned with traditional features (Siemieńska 2008). This statement found confirmation in the study of Donaldson et al (2017), who showed that social conservatism in Poland, defined as an adherence to traditional ideology, obtained a score of 4 of 5 (where 5 denotes the highest level of this country-level variable).…”
Section: Gender Issues In a Polish Contextmentioning
confidence: 97%
“…In the case of gender egalitarianism, Poland ranks 42nd of 149 countries in the world in the Global Gender Gap Report (World Economic Forum 2018), and this position is stable since 2006 (44th of 115 countries). Some researchers pointed out that although values and attitudes toward family and work are still changing after the political transformation in Poland, gender roles seem to still be strongly aligned with traditional features (Siemieńska 2008). This statement found confirmation in the study of Donaldson et al (2017), who showed that social conservatism in Poland, defined as an adherence to traditional ideology, obtained a score of 4 of 5 (where 5 denotes the highest level of this country-level variable).…”
Section: Gender Issues In a Polish Contextmentioning
confidence: 97%
“…Social norms of behavior, working rules, values, parental and gender roles that successfully organized the life of individuals and their families for the last fifty years during the collectivistic communist culture became non-adaptive and useless. This phenomenon, defined in terms of social anomy, must have had an impact on the family processes, especially with regard to the family orientation which is considered to be the core for Polish culture (Boski, 2009;Inglehart & Welzel, 2005;Nowak, 1979;Siemieńska, 2008). Social anomy may lead to differences in attachment.…”
Section: Brief Introduction Of the Cultural Changes In Polandmentioning
confidence: 99%
“…In addition, the increase in the level of education and growing aspirations of women motivates them to become more involved in the public sphere (Siemieńska 2008). However, it has to be noted that traditional farming was based on the significant contributions of all family members, which did not really fit the simplistic traditional family model.…”
Section: Drivers Of Feminization and Its Consequencesmentioning
confidence: 98%